KRISIS KETELADANAN DI ERA DIGITAL DAN UPAYA PENGUATAN AKHLAK MELALUI PENDIDIKAN AGAMA ISLAM - Nurlida Asni; Deli Asmawati Siregar; Emmi Fauziah Siregar; Mutiara Rahmadani Sagala (Yayasan Baitul Hikmah al-Zain, 2026)
This ournal examines the crisis of exemplary conduct that loccurs in the diaital era and explores various efforts to strenathen morality through Islamic Reliaious Education (PAI). In today's digital age, the rapid flow of information and limitless social interaction have changea the way people think, communicate, and behave. However behind these conveniences and technological advancements lie serious challenges related to moral degradation and the weakening of ethical values among individuals, especially the younger generation. This study employs a qualitative method with a library research approach to analyze literature, previous studies, ana empirical data related to the crisis of exemplary conduct and the role of PAI in fosterina moral awareness. The findinas indicate that the moral crisis in the diaital era is influenced by several factors, including the negative impact of social media, uncontrolled access to information, lack of character education, weakened family supervision, exposure to inappropriate foreign cultures, and weak enforcement of moral discipline. To address these problems, it is necessary to strengthen morality through PAI by integrating Islamic values into learning, emphasizing teacher exemplary behavior, habituating students to good deeds, encouraging positive and wise use of diaital media, and buildina collaboration between schools and parents. In addition, continuous monitoring and evaluation of moral development programs are crucial. Through these comprehensive efforts, PAI is expected to build a strong moral foundation, enablina the younger generation to resist negative influences, uphola Islamic ethics, and make wise and responsible decisions in their daily lives